A methodology for loss and performance assessment of a variable geometry turbocharger turbine through a new meanline FORTRAN program. Issue 4 (11th November 2021) - Ketata, Ahmed; Driss, Zied
Abstract : Purpose: Variable geometry turbine (VGT), a key component of modern internal combustion engines (ICE) turbochargers, is increasingly used for better efficiency and reduced exhaust gas emissions. The aim of this study is the development of a new meanline FORTRAN code for accurate performance and loss assessment of VGTs under a wider operating range. This code is a useful alternative tool for engineers for fast design of VGT systems where higher efficiency and minimum loss are being required. Design/methodology/approach: The proposed meanline code was applied to a variable geometry mixed flow turbine at different nozzle vane angles and under a wide range of rotational speed and the expansion ratio. The numerical methodology was validated through a comparison of the predicted performance to test data. The maps of the mass flow rate as well as the efficiency of the VGT system are discussed for different nozzle vane angles under a wide range of rotational speed. Based on the developed model, a breakdown loss analysis was carried out showing a significant effect of the nozzle vane angle on the loss distribution. Findings: Results indicated that the nozzle angle of 70° has led to the maximum efficiency compared to the other investigated nozzle vane angles ranging from 30° up to 80°. The results showed that the passage loss was significantly reduced as the nozzle vane angle increases from 30° up to 70°. Originality/value: This paper outlines a new meanline approach for variable geometry turbocharger turbines. The developed code presents the novelty of including the effect of the vane radii variation, due to the pivoting mechanism of the nozzle ring. The developed code can be generalized to either radial or mixed flow turbines with or without a VGT system.